Effect of broad-leaved dock (Rumex obtusifolius L.) on grass silage quality - Hejduk, Stanislav; Doležal, Petr (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2014)
The effect of broad-leaved dock (BLD) on nutritive value and fermentation process of grassland forages was studied together with the effect of formic acid addition (4.0 vs. 2.0 l.t−1) and inoculation by lactic acid bacteria (LAB). Herbage of dock exhibits low DM content, crude protein and fibre contents, yet its NEL concentration is low.Despite of the low DM content in BLD silages, the fermentation process was successful, but the silages show significantly higher contents of lactic acid (176.5 %), acetic acid (198.2 %) and lover pH values (4.24 vs. 4.39) as compared with than the grass silage. Silages made of dock do not contain butyric acid and exhibit low rates of proteolysis (9.2 % NH3 from total N). Addition of formic acid shows in the group of assessed silages significant reduction content of lactic acid (−6.5 %) and acetic acid (−9.3 %) and significant decrease of pH value (−0.05). The use of probiotic preparation leads to significantly higher lactic acid production (+39.3 %) and to lover pH value (−0.23) as compare with control without additions.